Karakteristik dewan komisaris dan manajemen laba: bukti pada peristiwa penawaran saham perdana - Doddy Setiawan (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2018)
This research aims at examining the effect of board of commissioners characteristics on earnings management in the context of Initially Public Offering (IPO). There are five characteristics of board of commissioners, including: board of commissioners size, percentage of independent commissioners, female commissioners, age and tenure of board of commissioners. Sample of the study consist of 161 non-financial firms that engage in IPO during 2001 – 2016 periods. The result of the study shows female commissioners, independent commissioners, board commissioners size and tenure have no significant effect on earnings management. However, age provide significant effect to mitigate earnings management during IPO. Commissioners with higher age have effectively reduce earnings management. The commissioners use their experience to mitigate earnings management. Further, the study divide sample of the study into larger firms and smaller firms. The result shows that female commissioners and board of commissioners size have negatif effect on earnings management. However, independent commissioners might not have effectively monitor earnings management. Further, age and tenure of the board of commissioners have no significant effect on earnings management in larger firms. The study find that independent commissioners and age have effectively mitigate earnings management in the smaller firms that conducted IPO. Therefore, it is important to consider size of the firm to analyze the effect of board of commissioners characteristics on earnings management during IPO process.